2012
DOI: 10.5897/ajar11.817
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of five bambara groundnut (Vigna subterranea (L.) Verdc.) landraces to heat and drought stress at Tono-Navrongo, Upper East Region of Ghana

Abstract: The need to obtain crop varieties that are tolerant to heat and drought cannot be overemphasised especially with the threat of climate change to agricultural productivity in sub-Saharan Africa. Bambara groundnut has been identified as a drought tolerant crop; however, variations exist among landraces with respect to drought tolerance. An experiment was therefore conducted to evaluate the performance of five bambara groundnut landraces: Black eye, Burkina, NAV 4, NAV Red and Tom, to drought and heat stress, at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 19 publications
2
17
0
1
Order By: Relevance
“…Reduced plant height, leaf number and LAI constitute this adaptation aimed at minimising water loss under drought stress (Mitchell et al 1998). Similar results showing reduction in plant height, leaf number and LAI in bambara groundnut were found in the literature (Collinson et al 1996, 1997, 1999, Sesay et al 2004, Mwale et al 2007, Vurayai et al 2011a, 2011b, Berchie et al 2012.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Reduced plant height, leaf number and LAI constitute this adaptation aimed at minimising water loss under drought stress (Mitchell et al 1998). Similar results showing reduction in plant height, leaf number and LAI in bambara groundnut were found in the literature (Collinson et al 1996, 1997, 1999, Sesay et al 2004, Mwale et al 2007, Vurayai et al 2011a, 2011b, Berchie et al 2012.…”
Section: Discussionsupporting
confidence: 75%
“…Water stress occurring at any stage can have a negative impact on yield. Several studies described the germination, growth and yield responses of bambara groundnut landraces to water stress (Collinson et al 1996, 1997, 1999, Sesay et al 2004, Mwale et al 2007, Vurayai et al 2011a, 2011b, Berchie et al 2012), but information describing local bambara groundnut landraces is scarce. Collinson et al (1997) reported that drought tolerance in a Zimbabwean cream bambara groundnut landrace was the result of an ability to maintain leaf turgor pressure through a combination of osmotic adjustment, reduction in leaf area and effective stomatal control.…”
mentioning
confidence: 99%
“…Selon les producteurs, le voandzou n'est pas produit au sud parce que les parents n'ont pas intégré cette culture dans leur habitude et aussi les conditions climatiques ne s'y prêtent pas quand bien même beaucoup estiment que le voandzou s'adapte plus facilement aux conditions difficiles surtout à la sécheresse et au sol pauvre (Obagwu, 2003 ;Basu et al, 2007). Une tendance similaire est observée au Ghana (Berchie et al, 2012) et en Tanzanie (Ntundu et al, 2006). Le niébé est aujourd'hui la deuxième légumineuse après l'arachide selon les producteurs.…”
Section: Discussionunclassified
“…From the results of Mabhaudhi et al, (2013), bambara groundnut was observed to have drought escape mechanisms where, under drought stress, it had a shortened vegetative growth period, early flowering, reduced reproductive stage and early maturity in order to minimise the adverse effect of drought on plant development. Higher root dry weight was reported when bambara groundnut landrace, Burkina (originally from Burkina Faso), was subjected to drought (Berchie, 2012). Denser and deeper root growth will allow the plant to utilise more soil moisture under drought stress.…”
Section: Effect Of Drought Stress On Bambara Groundnutmentioning
confidence: 99%